2016
DOI: 10.1515/jvetres-2016-0055
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the natural hormones 17β-oestradiol and testosterone in serum of cattle: results from population studies in Poland

Abstract: Introduction: The present study is a comprehensive overview of the natural occurrence of 17β-oestradiol and testosterone in serum of cattle in Poland. Material and Methods: The serum samples (n = 826) were collected from cattle within five years. The samples were examined for the presence of oestradiol and testosterone using ELISA or gas chromatography with mass spectrometry. Results: In 98 samples (24%) 17β-oestradiol was detected above decision limits of applied methods, including five samples over the recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…In 66 male serum samples, 17β-testosterone was detected at concentration levels above the LOQ value, and the results of the confirmatory analysis for 17β-testosterone were reported in Table 2. The data obtained were in accordance with previous studies [16,17], and confirm that the values in calves were below the limits indicated in the national legislation [7].…”
Section: Blood Serum Sample Analysissupporting
confidence: 91%
“…In 66 male serum samples, 17β-testosterone was detected at concentration levels above the LOQ value, and the results of the confirmatory analysis for 17β-testosterone were reported in Table 2. The data obtained were in accordance with previous studies [16,17], and confirm that the values in calves were below the limits indicated in the national legislation [7].…”
Section: Blood Serum Sample Analysissupporting
confidence: 91%